Expressing evaluation across disciplines in primary and secondary CLIL writing: a longitudinal study. Issue 3 (16th March 2023) - Whittaker, Rachel; McCabe, Anne
ABSTRACT: The construct of cognitive discourse functions (CDFs) has been proposed as a bridge between linguists and educationalists, linking 'subject specific cognitive learning goals with the linguistic representations they receive in classroom interaction' (Dalton-Puffer 2013. "A Construct of Cognitive Discourse Functions for Conceptualising Content-Language Integration in Q4 CLIL Multilingual Education." EuJAL 1 (2): 216–253, 220). We focus on the CDF evaluate, using the Appraisal model to analyze evaluative language in a longitudinal corpus of student texts written in L2 English across disciplines (natural science, history, art), collected from the same students at the end of primary school (aged 11+) and at the beginning and end of secondary year 2 (aged 13–14). We trace students' control of meaning-making resources for the CDF evaluate across disciplines and over time through their ability to 'couple' interpersonal, or evaluative, meanings with their ideational, or field-specific knowledge. The findings show some development towards appropriate field + evaluation couplings, and suggest ways teachers can focus students' attention on the language of evaluation across disciplines, aiding development of cognitive discourse competence. Our study further supports the contributions of Systemic Functional Linguistics to educational contexts, as the Appraisal framework discriminates types of evaluation for creating disciplinary knowledge.